MODEL KONFIGURASI STRUKTUR KURIKULUM PROGRAM STUDI KEPENDIDIKAN ISLAM DI STAIN PURWOKERTO - Siswadi Siswadi (Jurnal Penelitian Agama, 1970)
Education plays an important role to meet the reguirements of the rapid progress of this modern era. To go along with this condition, the department of Islamic Education Management of STAIN Purwokerto should provide a curriculum accommodating to the demands of this era. The curriculum should be consistent with the vision and mission of STAIN Purwokerto so that it will be more effective. This article discusses the configuration of curriculum applied by the department of Islamic Education Management viewed from many aspects.